Limited-and Nonrecourse Project Finance: a Survey - Kleimeier, Stefanie (Estudios de Administración, 1995)
This paper reviews limited- and non-recourse project finance, a special financing approach for newly to be developed projects where the funds are directly linked to the cash flows of the project. This survey comprises a comprehensive literature review on project finance. Practitioner literature is reviewed with respect to project risks and hedging possibilities, project participants, the legal framework of the project company, the financial elements, and a special form of project finance: the build-operale-transfer model. Next to practitioner oriented literature, the academic literature is reviewed which models project finance as an element of a capital structure equilibrium. An appendix lists references of practitioner's articles on project finance and thus allows the reader to gather information about specific areas in project finance, for example with respect to requirements for project finance in various industries or countries.